Pembatasan Hak Atas Informasi Publik Di Indonesia - Gusman, Delfina (UIR Press, 2022)
In principle any public information is open and accessible public information by each user , in addition to being excluded is the secret information in accordance with the act , propriety , and the public interest .Public information and the tight nature of being excluded limited. Restriction rights over the information in certain conditions can be justified , because the right to information not included in the right that cannot be reduced in the condition of anything ( non-derogable rights)